The behavior therapist´s interpretation: an exploratory study (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
The purpose of this study was to exam a female behavior therapist trainee’s interpretative verbal behavior during 14 psychotherapy sessions with an adult woman. These sessions were recorded and transcribed. The analyses of the therapist’s verbal repertoire showed the following categories related to her therapeutic performance: information, investigation, interpretation, advice, and consequencing. The results showed that the prevalent category was investigation and that interpretations occurred in 21,52% of the analysed utterances mostly along with other therapist’s performance functions. So five interpretative categories related to these functions were identified: informative, investigative, explanatory, advisory, and consequencial interpretation. The results also demonstrated that the therapist interpreted mainly with the function of conducting investigations (31,40%) but many of her utterances also included explanatory interpretations (24,41%). Some variables that possibly control the therapist´s interpretative verbal behavior were identified.